Physico-chemical and Nutritional Evaluation of Cookies with Different Levels of Rosehip and Hibiscus Powder Substitution - Surbhi Antarkar; Anurag Sharma; Anushka Bhargava; Honey Gupta; Ritu Tomar; Sakshi Srivastava (Archives of Current Research International, 2019)
Aim: Food with high nutritional value is in great demand for proper functioning of body systems and potential health benefits. As a result, value-added foods or functional foods with higher level of dietary fiber and antioxidant have developed, especially in bakery products such as cookies. This study was aimed to develop and evaluate proximate composition, phenolic compounds, vitamin C content and sensory acceptance of cookies. Study Design: The formulations were prepared (20% rosehip powder and 15% hibiscus powder in formulation CF1, 15% rosehip powder and 20% hibiscus powder in formulation CF2, 15% rosehip powder and 15 % hibiscus powder in formulation CF 3) in a standard cookie recipe. Place and Duration of Study: Department Of Food Technology, ITM University Gwalior, Madhya Pradesh, (India), between June 2018 to February 2019. Methodology: The proximate analysis,phytochemical analysis and sensory analysis of cookies was done using standard AACC International procedures. Results: Cookies prepared from formulation second (15% rose hips and 25% hibiscus powder) was more acceptable than other formulations on the basis of sensory evaluation. Conclusion: The analysis revealed that the increment in substitution in flour has increased the health benefits of cookies when compared to control cookies. The substitution with Rose hips and Hibiscus powder has a significant share in enhancing the TPC content, Total antioxidant capacity and other bioactive compounds in cookies. For sensory quality the CF2 formulation (the overall acceptability) has found greatest in all formulations. Substitution with Rose hips and Hibiscus could bring much potential health benefits to the consumer by adding nutritional (crude fat, crude protein and crude fiber) as well as organoleptic properties.